Brushless Synchronous Machine With Dual-Frequency Inverter for High Torque and Low Ripple Operation - Hafiz Mudassir Munir; Qasim Ali; Jose Rodriguez; Mohamed Abdelrahem (IEEE Access)
In this paper, a novel brushless synchronous machine topology is introduced with the integration of a double-frequency inverter system, which plays a pivotal role in generating a sub-harmonic magnetomotive force (MMF) that significantly enhances torque performance. There are two different windings on the stator, ABC and XYZ winding, by operating the ABC winding at a fundamental frequency with an 8-pole configuration, and the XYZ winding at double the frequency with a 2-pole arrangement, the machine produces a sub-harmonic MMF that is one-fourth of the fundamental MMF. This precise sub-harmonic MMF control improves the interaction between the stator and rotor, inducing an electromotive force (EMF) in the rotor’s harmonic winding. The rotor employed here has two windings, harmonic and field windings. Harmonic winding induces the sub harmonic MMF and a rotating rectifier on the rotor coverts it to DC, feeding the DC current to field windings. The dual frequency inverter topology results in an improved rotor excitation and increased torque with lower ripple. The results from Finite Element Analysis (FEA) show the DF-BSM generates 12.65 Nm torque on average at 13.6% torque ripple and 80.7% operating efficiency making it superior to conventional brushless synchronous machines. Moreover, the Dual Frequency Brushless Synchronous Machine (DF-BSM) provides superior performance in brushless synchronous machines and is well suited for high torque, low noise applications where efficient brushless operation is critical.